Reliability and Validity of Work Life Balance Scale Indonesian Version - Gunawan, Gianti; Nugraha, Yus; Sulastiana, Marina; Harding, Diana (Journal of Research and Measurement in Psychology: JPPP, 2019)
Research on the reliability and validity of the work life balance construct is important considering that in Indonesia there is currently no instrument specifically used to measure or assess work life balance and because of the development of an understanding of the work life balance construct which always develops as a multidimensional construct. The subjects in this study were 460 employees of State-Owned Company in Bandung. The work life balance scale used in this study is an adaptation of the work life balance questionnaire developed by Gwenith G. Fisher, Carrie A. Bulger and Carlla S. Smith (in Journal of Occupational Health Psychology 2009, Vol. 14, No. 4, 441–456). In this study, the method of analysis is the confirmatory factor. The results showed that the items for the work life balance scale had SLF values ​​ranging from 0.75 to 0.912 so that all items could be said to be valid. CR value is 0.976 and VE is 0.707, which means a reliable work life balance scale. Work life balance scale is devided into two aspects, namely demands and resources. The demands aspect consists of 2 (two) sub aspects, namely work interference with personal life (PLIW) and personal life interference with work (PLIW) and. The second aspect, namely resources has 2 (two) sub aspects, namely work enhancement of personal life (WEPL) and personal life enhancement ofwork (PLEW).